2010
DOI: 10.5536/kjps.2010.37.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine Supplementation on Performance, Egg Quality, Blood Parameter and Liver Lipid and Lipid Peroxidation Levels of Laying Hens Fed High Fat Diet

Abstract: The current study was conducted to estimate the effect of dietary taurine on performance, egg quality, blood parameter, liver lipids and lipid peroxidation level of laying hens fed high fat diet. Two hundred eighty laying hens, forty five weeks of age, were allocated to four treatment groups with seven replicates of 10 each per treatment for 4 weeks. Experimental diets were assigned to each of the four groups: control diet (CON), CON with 0.5% taurine (CT), CON with 5% soybean oil (HF), and CON with 5% soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Several earlier studies showed that taurine supplementation had clear effect on reducing serum and liver cholesterol, triglycerides and atherosclerotic lipid accumulation (Matsushima et al, 2003;Militante & Lombardini, 2004). These results are consistent with the findings of Shim (2010) who observed that Tau supplementation improved serum total cholesterol and triglyceride concentration of laying hens fed high fat diet. A recent study showed that 0.20% taurine supplementation increased the content of serum HDL, serum lipoprotein lipase and liver hepatic lipase activity (Zeng et al, 2011) abc Means with different superscripts within the same column are significantly different (P <0.05).…”
Section: Resultssupporting
confidence: 88%
“…Several earlier studies showed that taurine supplementation had clear effect on reducing serum and liver cholesterol, triglycerides and atherosclerotic lipid accumulation (Matsushima et al, 2003;Militante & Lombardini, 2004). These results are consistent with the findings of Shim (2010) who observed that Tau supplementation improved serum total cholesterol and triglyceride concentration of laying hens fed high fat diet. A recent study showed that 0.20% taurine supplementation increased the content of serum HDL, serum lipoprotein lipase and liver hepatic lipase activity (Zeng et al, 2011) abc Means with different superscripts within the same column are significantly different (P <0.05).…”
Section: Resultssupporting
confidence: 88%